Maternal stature, maternal education and child growth in Pakistan: a cross-sectional study - Nazli Javid; Christy Pu (AIMS Press, 2020)
Pakistan has a significantly higher prevalence of stunted children under five years old compared with other countries with a similar income level. Given maternal education is a modifiable factor, we analyzed whether education has a larger marginal effect on improving children's growth for shorter stature mothers. Pakistan Demographic and Health Survey of 2012-13 was analyzed, with a total of 3,883 of children under five years of age (belonged to 2,327 mothers). The results showed that the overall prevalence of stunting, underweight, wasting, and overweight in our sample was 45%, 26.2%, 9.9%, and 9.5%, respectively. Short stature mothers have a higher number of malnourished children as compared to taller mothers. Compared to tall stature mothers, short stature mothers at all education levels have a higher number of stunted and underweight children. Maternal education has a significant positive effect on children's growth. However, we did not find significant differences in the marginal effect of maternal education among mothers with different statures. Policies providing specialized care to children born to short stature mothers are crucial, along with emphasizing mothers' education. Moreover, a poverty elevation program is necessary as a significant fraction of childhood malnutrition is attributed to the wealth index.